2022
DOI: 10.3389/fphar.2022.888563
|View full text |Cite
|
Sign up to set email alerts
|

Association of TGF-β Canonical Signaling-Related Core Genes With Aortic Aneurysms and Aortic Dissections

Abstract: Transforming growth factor-beta (TGF-β) signaling is essential for the maintenance of the normal structure and function of the aorta. It includes SMAD-dependent canonical pathways and noncanonical signaling pathways. Accumulated genetic evidence has shown that TGF-β canonical signaling-related genes have key roles in aortic aneurysms (AAs) and aortic dissections and many gene mutations have been identified in patients, such as those for transforming growth factor-beta receptor one TGFBR1, TGFBR2, SMAD2, SMAD3,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 118 publications
(130 reference statements)
0
12
0
Order By: Relevance
“…The TGF-β signaling pathway is significant for the maintenance of normal structure and function of the aorta [35] , and genetic evidence suggests that TGF-β signaling-related genes play an important role in AD, such as mutations in genetic specimens from patients with AD, often accompanied by paradoxically enhanced TGF-β signaling [36] . Chen et al [37] then performed a target sequencing that showed that activation of the TGF-β signaling pathway may be related to the pathogenesis of AD.…”
Section: Resultsmentioning
confidence: 99%
“…The TGF-β signaling pathway is significant for the maintenance of normal structure and function of the aorta [35] , and genetic evidence suggests that TGF-β signaling-related genes play an important role in AD, such as mutations in genetic specimens from patients with AD, often accompanied by paradoxically enhanced TGF-β signaling [36] . Chen et al [37] then performed a target sequencing that showed that activation of the TGF-β signaling pathway may be related to the pathogenesis of AD.…”
Section: Resultsmentioning
confidence: 99%
“…In the research literature, studies focused on the role of TGFalpha in AAA are limited, whereas TGF-beta 1 signaling has been intensively studied on this topic. Some hypotheses about the role of TGF-beta 1 in the development of aneurysm have been proposed; however, there are some controversies [45].…”
Section: Discussionmentioning
confidence: 99%
“…A single transmembrane protein with a cytoplasmic serine/threonine kinase domain. Loss of function mutations in the gene encoding TGF-βR2 cause LDS (25).…”
Section: Tgf-βr2mentioning
confidence: 99%